Th17 and Treg Balance in Children With Obesity and Metabolically Altered Status - Calcaterra, Valeria; Croce, Stefania; Vinci, Federica; De Silvestri, Annalisa; Cordaro, Erika; Regalbuto, Corrado; Zuccotti, Gian Vincenzo; Mameli, Chiara; Albertini, Riccardo; Avanzini, Maria Antonietta (Frontiers in Pediatrics, 2020)
Background: Chronic low-grade inflammation and activation of the immune system are hallmark pathogenic mechanisms involved in metabolic dysfunction related to obesity. In particular, the involvement of regulatory and pro-inflammatory lymphocyte subpopulations has been reported in adults. We evaluated the Th17/Treg lymphocyte balance in obese and normal weight children, in relation with their metabolic status. Methods: We enrolled 50 pediatric patients. According to metabolic status, subjects were classified into: metabolically healthy (MH) and metabolically unhealthy (MU) groups. MU phenotype was defined as the presence of at least one of the following risk factors: blood pressure >90th percentile, glycemia>100 mg/dl, HDL cholesterol<40 mg/dl, triglycerides>100 mg/dl (<10 years) or >130 mg/dl (>10 years), impaired insulin sensitivity with HOMA-IR>97.5th percentile. Patient Treg and Th17 profiles were also evaluated. Results: Based on the presence of metabolic and/or cardiovascular pathological parameters, 15 MU (30%) and 35 MH (70%) children were detected; all MU children were obese. Analyzing the correlations between lymphocyte subpopulations and metabolic data, we noted a correlation between Th17 percentage and systolic hypertension (p=0.01, r -0.37); Treg/Th17 ratio and HOMA-IR (p=0.02, r= 0.32) and systolic hypertension (p=0.05, r= 0.30). Conclusion:Children with obesity have a high risk of developing metabolic and cardiovascular complications. The Th17/Treg lymphocyte balance appears to be involved in glycemic homeostasis and blood pressure control. Careful and early monitoring of the immune system would facilitate new early preventive strategies in pediatric metabolic diseases.